Peran Guru PPKn dalam Meningkatkan Karakter Disiplin Siswa di SMAN 06 Mataram - Alambana, Bondan Muhammad; Mustari, Mohamad; Hadi, Muhamad Samsul (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2024)
This study aims to examine the role of PPKn teachers in shaping students' discipline. The research was conducted at SMAN 06 Mataram using a qualitative approach and case study method. Data collection involved interviews, observations, and documentation. The findings reveal that PPKn teachers play key roles, including being creative and innovative educators, serving as role models, and enforcing discipline through Kebun Bina Karakter, a program where students engage in farming activities as a form of sanction for indiscipline. However, challenges persist, primarily due to the influence of technology, such as mobile phones, which make it difficult for students to distinguish between right and wrong. Furthermore, many students lack clear life goals. The study concludes that PPKn teachers have effectively contributed to enhancing students' discipline at SMAN 06 Mataram. Future research could explore how integrating positive technology use that can further strengthen students' discipline in the face of digital-era challenges.